Enhancement of Passive Sliding Mode Control Model for LVRT Capability in DFIG Based Wind Turbines - M. Kenan Döşoğlu (Wind Energy)
ABSTRACT Doubly fed induction generator (DFIG) is vulnerable to transient stability situations occurring on the grid side. First of all, with the models to be developed in the wind turbines, LVRT capability must be provided depending on the grid code requirement for various problems that may occur, such as overcurrent, voltage, and uncertainty in parameters. For this purpose, in this study, a passive sliding mode control (PSMC) model in the rotor side converter (RSC) was developed to control the power flow between DFIG and the grid during transient stability. In addition, the aim was to provide stator–rotor electromotive force (emf) models in DFIG to dampen the oscillations that occur as a result of faults on the grid side and to enable the simulation program to make smooth calculations. Comparisons of proposed models with traditionally used models in various faults were made, and the results were interpreted in detail. As a result of the obtained results, it was seen that the intended approaches stabilized the system in a short time, and the oscillations were quickly damped.